Brain Injury as a Neurodegenerative Disorder - Robin E.A. Green (Frontiers Research Topics, 2017)
It has been long assumed that following the resolution of acute injuries, traumatic brain injury represents a stable neural entity. However, there is growing evidence that a single moderate-severe brain injury may instead trigger an ongoing deteriorative process that commences sub-acutely, and occurs regardless of age. For scientists and clinicians, it is critical to examine this body of evidence and to explore its implications. Do the findings represent a neurodegenerative process or can they be alternatively explained? What are the neural, behavioural and functional characteristics of this progressive deterioration? Such information is needed to develop treatments to prevent or mitigate decline, and to inform the clinical care of brain injured patients. Research and clinical practice are influenced by the assumption that moderate-severe TBI is non-progressive, with few studies exploring treatments to prevent progression, and rehabilitation typically concentrated in the early stages of injury. Brain injuries can never be fully prevented. However, understanding that such progressive deterioration occurs opens a novel area of research - prevention of secondary decline - offering new possibilities for the improvement of long-term outcomes in people with traumatic brain injury.